A significant improvement of scheelite flotation efficiency with etidronic acid. (10th April 2018) - Kang, Jianhua; Hu, Yuehua; Sun, Wei; Liu, Runqing; Yin, Zhigang; Tang, Honghu; Meng, Xiangsong; Zhang, Qingpeng; Liu, Hang
Abstract: This research demonstrates an effective application of etidronic acid to improve the scheelite flotation efficiency and reduce the consumptions of energy and reagents. The cleaning recovery is significantly increased by 7%, and the cleaning cost is reduced by 17% accompanied with the efficient improvement of roughing grade from 1.22% to 1.68% compared with that in previous month. The depression abilities of etidronic acid, normal water glass, and acidified water glass for the scheelite roughing flotation are studied using laboratory-scale experiments. Etidronic acid shows an improved selective performance in improving the roughing grade. This performance is further verified by industrial test. The use of etidronic acid in the roughing circuit improves the product grade from 24.66% to 28.26%. The daily product output is also increases by 1.54 t. Economic evaluation results indicate that the heating cost is reduced by 28%, and the water glass consumption is decreased by 14%. An increased product profit of $1, 248, 000 and a reduced cost of $20, 841 are also obtained. Graphical abstract: Highlights: An original depressant is utilized to improve scheelite flotation performance. Etidronic acid shows an efficient performance on flotation efficiency improvement. The production cost related to heating and reagents is remarkable reduced by 17%. A significant economic profit is achieved with the increase of product output. This application will promote the sustainable development of resource and energy.